Potential of porous media combustion technology for household applications. - Malico, Isabel (2015)
Households are major energy consumers and have a significant contribute to the World’s final energy consumption and CO2 emissions. Among the energy end-use in buildings lies cooking. The energy saving potential of cooking appliances is large and an investment on the development of more efficient and less polluting stoves and ovens is necessary. Porous medium combustion, already commercially available for several other applications, is a promising technology that can be applied also to household cooking. This paper reviews the research works done in the field. The number of papers dedicated to this specific application is relatively low, and most of them concentrate on experimentally proving the advantages of porous burners when compared to conventional solutions. The influence of burner characteristics and operating conditions are analysed in a few studies. However, there is still a considerable scope for the development of enhanced porous burners for household applications.